Centralizing culture in cultural sport psychology research: The potential of narrative inquiry and discursive psychology. (March 2015) - McGannon, Kerry R.; Smith, Brett
Abstract: Objectives: To understand cultural issues within cultural sport psychology (CSP) research, methodological variation has been advocated. Those interested in carrying out CSP research with a 'critical sensibility' are presented with the challenge of deciding what methodology may capture a socially constructed and nuanced analysis of culture, self-identity and experience. In this paper we focus on two qualitative methodologies grounded in social constructionism and their potential for advancing understandings of culture within CSP research: narrative inquiry and discursive psychology. Results: Focusing on what is at the "core" of critical CSP research – cultural praxis – we briefly outline narrative inquiry and discursive psychology, articulate three key convergences between them and discuss how these link with, and build upon, cultural praxis tenets. To further demonstrate the potential of these methodologies for centralizing and expanding understandings of culture in CSP, we next offer distinct methodological contributions of each: autoethnography, conversation analysis, and critical discourse analysis. Conclusion: We close by suggesting that to move beyond theoretical discussions of cultural praxis in CSP, sport psychology researchers might use narrative inquiry and discursive psychology. Doing so allows for more informed and principled methodological choices in CSP research that align with social constructionism, and provides a critical and nuanced analysis of culture, moving forward. Highlights: We expand dialogues advocating for critical forms of cultural sport psychology research. Two social constructionist methodologies aligning with cultural praxis are outlined. Narrative inquiry's and discursive psychology's focus on language centralizes culture. Informed and reflexive methodological choices in CSP research are encouraged.